INTRA-ARTICULAR PIROXICAM AND TRIAMCINOLONE IN A RAT MODEL OF OSTEOARTHRITIS; ELEVATION AND COMPARISON OF CHONDROPROTECTIVE EFFICACY - Ishaq, Noaman; Ata, Nausheen; Saqib, Maryam; Shaheen, Bushra; Zafar, Ayman; Malik, Ashwa (Journal of Ayub Medical College Abbottabad, 2021)
Background: Osteoarthritis is the most common chronic degenerative joint disease. Definite treatment of osteoarthritis is still undiscovered. This study was designed to evaluate and compare the chondroprotective efficacy of piroxicam and triamcinolone in rat model of osteoarthritis. Methods: This laboratory based experimental study was conducted in Pharmacology Department, Army Medical College, Rawalpindi, from April-June 2019. Osteoarthritis was induced by medial meniscectomy and anterior cruciate ligament resection in knee joints of twenty-four rats. They were divided in three groups with eight rats in each. Group I, II and III were control, piroxicam and triamcinolone groups that were treated by intra articular saline, piroxicam and triamcinolone once weekly for four weeks respectively and then gait pattern was scored. Animals were euthanized thereafter and samples were taken for histopathological analysis. Results: Comparison of gait score of control, piroxicam and triamcinolone groups exhibited a p-value of <0.01. Intergroup comparison of gait of group I and II, group I and III and group II and IV depicted p-value of <0.001,0.013 and 0.013 respectively. Likewise histopathological comparison of control, piroxicam and triamcinolone groups showed p-value of <0.01. While Intergroup histopathological comparison of group I and II, group I and III and group II and IV showed p-value of <0.001, <0.001 and 0.008 respectively. conclusion: Comparison of control group with treatment group proved chondroprotective efficacy of piroxicam and triamcinolone. On comparison of treatment groups, it was concluded that piroxicam has better chondroprotective efficacy as compared to triamcinolone.